A generalized approach for selecting solar energy system configurations for a wide range of applications. (2019) - Doron, Pinchas; Karni, Jacob; Slocum, Alexander
ABSTRACT: Abstract : A systematic, objective approach for selecting the most suitable solar energy system in a large and diverse range of applications is presented. The definition of Levelized Energy Cost (LEC) is modified/extended, including a Societal Impact Factor (SIF). The use of the methodology is demonstrated for a specific case. The method can be used for selecting an optimal system configuration and for identifying research and development directions . A systematic and objective approach for selecting the most suitable solar energy system for a large and diverse range of applications is presented. The main parts of the approach are: (i) Define the project objectives and fundamental system design requirements. (ii) Establish a reliable and objective method for determining and comparing energy costs. (iii) Follow a well-defined methodology for obtaining a configuration that meets the system objectives and complies with all the design requirements, at a minimum energy cost. These parts are divided into discrete steps, which emphasize meeting the project objective and design requirements. The definition of the main cost comparison metric, the Levelized Energy Cost (LEC), is modified to include the ratio between energy sold and energy production capacity, and a Societal Impact Factor (SIF) for health, environmental, societal, political and cultural aspects. Application of the method is demonstrated for a specific case—a system whose objective is "providing an extensive and reliable supply of renewable energy, aiming to gradually replace most or all of the fossil fuel combustion in a highly populated region." As shown, the process can serve dual purposes, (i) finding the most suitable system configuration and (ii) pointing out vital research and development objectives. The suggested method is also applicable to complex energy conversion configurations, such as hybrid or symbiotic systems.